2018
DOI: 10.1001/jamapediatrics.2018.0228
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Powered Oxygen Delivery in Low-Resource Settings

Abstract: Oxygen is an essential medicine for life-threatening hypoxemic illnesses, including pneumonia, which is currently the leading cause of childhood mortality worldwide. 1,2 However, oxygen is not available in many pediatric wards in lowincome countries. In a survey of 12 African countries, only 44% of 231 health centers, district hospitals, and provincial or general hospitals had access to oxygen on a continuous basis. 3 Pragmatic solutions are needed to improve access to oxygen in low-resource settings. In resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 5 publications
0
25
1
Order By: Relevance
“…A multi-hospital effectiveness study in Papua New Guinea demonstrated a reduction in mortality from childhood pneumonia from 5.0% to 3.2% (35% reduction in mortality) after implementation of an enhanced O 2 delivery system [13]. We have previously described and implemented a novel strategy for O 2 delivery that could be implemented in remote locations with minimal access to an electrical power supply: solar-powered oxygen (SPO 2 ) delivery [14,15]. SPO 2 is an effective solution for supplemental O 2 in low-resource settings [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A multi-hospital effectiveness study in Papua New Guinea demonstrated a reduction in mortality from childhood pneumonia from 5.0% to 3.2% (35% reduction in mortality) after implementation of an enhanced O 2 delivery system [13]. We have previously described and implemented a novel strategy for O 2 delivery that could be implemented in remote locations with minimal access to an electrical power supply: solar-powered oxygen (SPO 2 ) delivery [14,15]. SPO 2 is an effective solution for supplemental O 2 in low-resource settings [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described and implemented a novel strategy for O 2 delivery that could be implemented in remote locations with minimal access to an electrical power supply: solar-powered oxygen (SPO 2 ) delivery [14,15]. SPO 2 is an effective solution for supplemental O 2 in low-resource settings [14][15][16]. Our systems have been described in detail previously and implemented at two hospitals in Uganda [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations